2022
DOI: 10.3390/ma15144805
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of 3D Printed Ti6Al4V Gyroid Lattices with Varying Porosity

Abstract: Corrosion of medical implants is a possible failure mode via induced local inflammatory effects, systemic deposition and corrosion related mechanical failure. Cyclic potentiodynamic polarisation (CPP) testing was utilized to evaluate the effect of increased porosity (60% and 80%) and decreased wall thickness in gyroid lattice structures on the electrochemical behaviour of LPBF Ti6Al4V structures. The use of CPP allowed for the landmarks of breakdown potential, resting potential and vertex potential to be analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…We investigated the following shapes in our animal experiments: gyroid, cube, cylinder, tetrahedron, double pyramid, and Voronoi ( Figure 1 ). Some of these shapes were chosen for comparison with those examined by several authors [ 6 , 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The degree of bone growth was determined using rivet-like cylindrical implants with a diameter of 6 mm and a rounded shape; these were used in the animal experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the following shapes in our animal experiments: gyroid, cube, cylinder, tetrahedron, double pyramid, and Voronoi ( Figure 1 ). Some of these shapes were chosen for comparison with those examined by several authors [ 6 , 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The degree of bone growth was determined using rivet-like cylindrical implants with a diameter of 6 mm and a rounded shape; these were used in the animal experiments.…”
Section: Methodsmentioning
confidence: 99%
“…They also concluded that the AM-manufactured Ti samples with larger porosity showed increased corrosion values; the optimum range of porosity was revealed to be between 40% and 60% [111]. In another study, Sharp et al [112] investigated the corrosion performance of AM-produced Ti6Al4V gyroid lattices with varied porosity values (60-80%). It was shown that the structure with 60% gyroid was susceptible to pitting corrosion in comparison to 80% gyroid and solid samples, mainly due to a higher lattice surface area to void volume ratio.…”
Section: Titanium and Its Alloysmentioning
confidence: 99%
“…It can also be observed that corrosion attacks mainly initiate and focus on special locations such as corners and raised edges. The solid sample manifested a very interconnected form, while the porous samples had distinct and isolated patches [112].…”
Section: Titanium and Its Alloysmentioning
confidence: 99%
“…There has been very few studies involving corrosion of additively manufactured Ti-6Al-4V lattices in the literature. Sharp et al [114] studied the effect of porosity on LPBF Ti-6Al-4V Gyroid structures and found out that a lower porosity lattice is more susceptible to pitting corrosion. This suggests a trade-off between lattice optimisation and corrosion behaviour and thus a potential link between void volume, surface area and corrosion.…”
Section: Corrosion In Am Latticesmentioning
confidence: 99%